Investigation of Natural Fibers as Ceiling Material - Beddu S.; Zainoodin M.M.; Muda Z.C.; Kamal N.L.M.; Mohamad D.; Mohamed Nazri F.; Naganathan S.; Husain N.M.; Sadon S.N. (Springer, 2023)
Bending strength; Ceilings; Energy efficiency; Fibers; Glass fibers; Natural fibers; Tensile strength; Building applications; Carboxymethyl cellulose; Flexural; Scirpus; Thickness; Tropical climates; Water absorption